Diatom Dominance Enhances Resistance of Phytoplanktonic POM to Mesopelagic Microbial Decomposition - Cabrera-Brufau, Miguel; Arin, Laura; Sala, Maria Montserrat; Cermeño, Pedro; Marrasé, Cèlia (Frontiers in Marine Science, 2021)
Particulate organic matter (POM) lability is one of the key factors determining the residence time of organic carbon (OC) in the marine system. Phytoplankton community composition can influence the rate at which heterotrophic microorganisms decompose phytoplankton detrital particles and thus, it controls the fraction of OC that reaches the ocean depths, where it can be sequestered for climate-relevant spans of time. Here, we compared the degradation dynamics of POM from phytoplankton assemblages of contrasting diatom dominance in the presence of mesopelagic prokaryotic communities during a 19-day degradation experiment. We found that diatom-derived POM exhibited an exponential decay rate approximately three times lower than that derived from a community dominated by flagellated phytoplankton (mainly coccolithophores and nanoflagellates). Additionally, dissolved organic matter (DOM) released during the degradation of diatom particles accumulated over the experiment, whereas only residual increases in DOM were detected during the degradation of non-diatom materials. These results suggest that diatom-dominance enhances the efficiencies of the biological carbon pump and microbial carbon pump through the relatively reduced labilities of diatom particles and of the dissolved materials that arise from their microbial processing.